Tanggap Pertumbuhan Dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Waktu Aplikasi Dan Konsentrasi Pupuk KNO3 - Anwar Koheri; Mariati Mariati; Toga Simanungkalit (Jurnal Agroekoteknologi, 2015)
The purpose of the study was to determine the response of growth and yield of shallot (Alliumascalonicum L.) on time applications and KNO3 concentrations. The research was conducted at Pasar1 street No. 89 Tanjung Sari Medan, with a height of 25 metre above sea level, began from Julyuntil September 2013. The design of the research was a Randomized Block Design non factorialwith 13 treatments were: Control (without treatments); (KNO3 5 g/l water + application at 14, 21, 28,35 HST); (KNO3 5 g/l water + application at 14, 21, 28 HST); (KNO3 5 g/l water + application at 14,21 HST); (KNO3 5 g/l water + application at 14 HST); (KNO3 10 g/l water + application at 14, 21, 28,35 HST); (KNO3 10 g/l water + application at 14, 21, 28 HST); (KNO3 10 g/l water + application at14, 21 HST); (KNO3 10 g/l water + application at 14 HST); (KNO3 15 g/l water + application at 14,21, 28, 35 HST); (KNO3 15 g/l water + application at 14, 21, 28 HST); (KNO3 15 g/l water +application at 14, 21 HST); (KNO3 15 g/l water + application at 14 HST). Parameters observed wereplant height, tillers number, wet weight per sample, dry weight per sample, wet weight per plot anddry weight per plot. The results showed that all parameters observed were unsignificantly affectedby time applications and KNO3 concentrations except for plant height 5 – 7 weeks after planting.Key words : Shallot, time application, KNO3 fertilizer.